SELF-COMPASSION PASIEN DENGAN SAKIT HERNIA NUKLEUS PULPOSUS - Amita, Nindy (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
ABSTRACT Background: Self-compassion is a form of awareness of one's own situation and reducing and ending suffering within self. Someone with high self-compassion can be happier in life, including someone who is experiencing pain from Hernia Nucleus Pulposus (HNP). This study aims to determine the self-compassion of HNP patients who are undergoing medical rehabilitation therapy. Methods: This study uses a qualitative descriptive method with data collection techniques using observations, interviews and the self-compassion scale from Neff (2003) to determine the level of self-compassion of the subject. The subjects were 3 people with an age range of 53 – 58 years. The study was conducted from March to May 2021. Researchers selected 3 HNP patients who were very routine and came on schedule for medical rehabilitation therapy. Results: This study found 3 themes, namely (1) HNP patients know that their illness cannot be cured as before. (2) Patients routinely undergo physical therapy. (3) Patients believe that if they do treatment sincerely, they will feel calm and feel pain. The common humanity component is also a factor in being able to increase self-compassion in patients Conclusion: Patients who suffer from HNP are able to empathize with themselves, especially patients who are undergoing medical rehabilitation physical therapy. Keywords: Self-Compassion, Common Humanity, Hernia Nucleus Pulposus ABSTRAK Latar Belakang: Self-compassion merupakan bentuk kesadaran akan keadaan diri sendiri dan mengurangi serta mengakhiri penderitaan dalam diri. Seseorang dengan self-compassion yang tinggi dapat lebih bahagia dalam menjalani hidupnya, termasuk seseorang yang sedang mengalami nyeri Hernia Nucleus Pulposus (HNP). Penelitian ini bertujuan untuk mengetahui self-compassion pasien HNP yang sedang menjalani terapi rehabilitasi medik. Metode: Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data menggunakan observasi, wawancara dan skala self-compassion dari Neff (2003) untuk mengetahui tingkat self-compassion subjek. Subjek berjumlah 3 orang dengan rentang usia 53 – 58 tahun. Penelitian dilakukan pada bulan Maret hingga Mei 2021. Peneliti memilih 3 pasien HNP yang sangat rutin dan datang sesuai jadwal untuk terapi rehabilitasi medik. Hasil: Penelitian ini mendapatkan 3 tema yaitu (1) Pasien HNP mengetahui sakit yang dialami tidak dapat sembuh seperti sebelum sakit.. (2) Pasien rutin untuk melakukan terapi fisik. (3) Pasien yakin bahwa jika melakukan pengobatan dengan ikhlas maka diri menjadi tenang dan sakit tidak terasa. Komponen common humanity juga menjadi faktor dalam mampu meningkatkan self-compassion pada pasien Kesimpulan: Pasien yang menderita HNP mampu berempati terhadap dirinya sendiri terutama pasien yang sedang menjalani terapi fisik rehabilitasi medik. Kata kunci : Self-Compassion, Common Humanity, Hernia Nucleus Pulposus